Preserving the motif identity of Malaysian local block batik / Rabiatuadawiyah Mohd Kari - Mohd Kari, Rabiatuadawiyah (2020)
Generally, batik means 'tik' means 'to drip' or 'to drop'. Meanwhile, batik cap or block batik is a technique of wax - resist colour on a cloth made by pressing the fabric with a copper block. In the 1950s and 1960s, batik block with local identity was produced. Unfortunately, nowadays, Malaysian batik block does not portray a strong identity as compared to the Indonesian. Based on these problems, objective of this study is; to classify the various type of the local block batik motif and design base on characteristic and local features using suitable methodology to propose guideline. Hence, the aim of this study is to uplift the appreciation and awareness toward motif and design of local block batik identity among the society. The focus is at Terengganu and Kelantan. This qualitative study is in descriptive writing. Whereas, the sample technique is purposive sampling. This research used observation, document analyse and structured interview open ended with close ended. The data were gained from primary and secondary. The artefact are 421 of block batik motif. The typology analysis were used to classify motif and design of block batik (sarang) from 1920s until 2018s. The analysis Edmund Feldman, and Zakaria Ali theory were combined to analyse the motif and design of block batik fabric. The expected outcome is the guideline in designing block batik motif and design base on the Malaysia's identity. The recommendation for future study is the comparison of specific block batik identity at every district in Kelantan and Terengganu.